Prototype of Automatic Tomato Plant Watering Monitoring Tool Based on Telegram Using NodeMCU ESP8266 - Achmat Juliansyah; Muhammad Fahmi; Andi Yusika Rangan (Brilliance: Research of Artificial Intelligence, 2025)
The goal of this research is to design and develop a Telegram-based watering pump. This research aims to control and monitor soil moisture in tomato plants. To address this issue, an approach utilizing Arduino technology was used to create an attractive and efficient solution. This study analyzed the various components used in a Telegram-based tomato plant watering system. These components include the MCU8266 node, which connects or translates to a soil moisture sensor system used to measure soil moisture in tomato plants. The results of this research resulted in the successful design and implementation of a telegram-based tomato plant watering system. This system makes it easier for users to ensure the aerator remains operational. Black-box and white-box testing methods were used in this study to verify the system's functionality and security. Thus, this research provides a positive contribution to plantations in the Tanjung Batu PLTGU area through the application of innovative and efficient Arduino technology.